Analysis of Government Goods/Service Procurement Processes Through E-Purchasing System in the Environment Gorontalo Regency - Karla Utiarahman; Lisdawati Muda; Warno Panigoro (Journal of Economic, Business, and Administration (JEBA), 2021)
The purpose of this research is to find out: 1) the process of government procurement of goods/services through the E-Purchasing System in Gorontalo Regency; 2) Factors that Determine the Procurement Process of Government Goods/Services Through the E-Purchasing System in Gorontalo Regency. The research method used by the researcher is a qualitative method with a descriptive approach. The research approach used by this researcher is a descriptive approach method. Data analysis activities are carried out by means of data reduction (data reduction), data display (data presentation) and verification (verification). The results showed that the Government's Goods/Services Procurement Process Through the E-Purchasing System in Gorontalo Regency seen from the aspect of transparency was still lacking, integrity was still low and accountability was still low. -Purchasing or electronic catalogs are less effective; 2) The factors that determine the Government's Goods/Services Procurement Process Through the E-Purchasing System in the Gorontalo Regency environment include low resources, lack of transparency, bureaucratic structure is still slow to buy, disposition/attitude is still low, so it is not supportive Government Procurement Process of Goods/Services Through the E-Purchasing System.